RETHINKING LEGISLATIVE TERM LIMITS: SAFEGUARDING DEMOCRATIC RENEWAL IN CONSTITUTIONAL STATE OF INDONESIA - Ristyawati, Aprista; Utama, Yos Johan; Wardhani, Lita Tyesta Addy Listya; Hanum, Willy Naresta (Fakultas Hukum, Universitas Diponegoro, 2025)
Indonesia’s constitutional framework enshrines the separation of powers among the executive, legislative, and judicial branches, yet only the legislature lacks explicit term‐limit provisions for its members. This normative legal analysis examines the democratic and legal implications arising from this regulatory gap and proposes strategies to safeguard legislative renewal. Utilizing primarily on secondary sources—statutes, academic literature, and comparative analyses—the research employed both statutory and conceptual approaches to assess existing laws, notably Law No. 17 of 2014 on the People’s Consultative Assembly and House of Representatives and Law No. 7 of 2017 on General Elections. The analysis identifies three core deficiencies: first, the lack of term limits undermines legal certainty by leaving tenure duration indeterminate and susceptible to arbitrary interpretation; second, unlimited re‐election fosters power entrenchment, increasing risks of corruption, collusion, and nepotism, and weakening the legislature’s oversight and budgetary functions; third, perpetual incumbency impedes generational renewal, diminishing internal party democracy and restricting political recruitment. Drawing comparative insights from Australia’s staggered Senate terms illustrate how structured tenure can promote dynamism while retaining institutional memory. In response, the study advocates for a clear legislative amendment that caps legislators’ service to two consecutive terms, aligned with principles of accountability, rotation of power, and open political recruitment. Additionally, it recommends that political parties institutionalize transparent internal mechanisms and enforce term‐limit rules to ensure cadre development and democratic governance. By codifying legislative term limits and fostering proactive party roles, Indonesia can strengthen constitutional checks and balances, enhance the legislative quality, and secure sustainable democratic renewal.